Laser Hole Drilling of Stainless Steel 321H and Steel 33 Using 3D CO2 Laser CNC Machine - Hussein, Furat I.; Taha, Ziad A.; Tawfiq, Thaier A.; Jawad, Ahmed B. (Iraqi Journal of Laser, 2011)
In present work an investigation for precise hole drilling via continuous wave (CW) CO2 laser at 150 W maximum output power and wavelength 10.6 μm was achieved with the assistance of computerized numerical controlled (CNC) machine and assist gases. The drilling process was done for thin sheets (0.1 – 0.3 mm) of two types of metals; stainless steel (sst) 321H, steel 33 (st). Changing light and process parameters such as laser power, exposure time and gas pressure was important for getting the optimum results. The obtained results were supported with computational results using the COMSOL 3.5a software code.